Ceramic particle reinforced iron-based composite material and preparation method thereof
The preparation of ceramic particle-reinforced iron-based composite materials through discharge plasma sintering technology solves the problems of reduced material performance and size limitation in traditional processes, realizes an efficient and environmentally friendly preparation process, and obtains materials with higher hardness and wear resistance.
Patent Information
- Application Number
- CN202510068040.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The traditional process of preparing particle-reinforced iron-based composites has the formation of too many carbide phases and intermetallic compounds, resulting in a degradation of material properties. The surface cladding method is only suitable for small-sized surface coatings, and large-sized bulk materials cannot be prepared.
Discharge plasma sintering technology is adopted, and after mixing Cr7C3 and TiC with Fe powder, it is pressed and packed tightly in a graphite mold, and then sintered in a discharge plasma sintering furnace, the sintering temperature is controlled to be 1100-1300°C, and the system sintering pressure is maintained at 30-40MPa.
It realizes the efficient preparation of ceramic particle-enhanced iron-based composite materials, with higher hardness and wear resistance, reduces energy consumption and environmental impact, is suitable for industrial production, and reduces the price of high-performance wear-resistant steel materials.
Smart Images

Figure BDA0005244841860000111 
Figure BDA0005244841860000121 
Figure HDA0005244841870000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials, and particularly relates to a ceramic particle-reinforced iron-based composite material and a preparation method thereof. Background Art
[0002] Particle-reinforced iron-based composite materials mainly refer to material systems in which ceramic particles are dispersed in the iron matrix in the form of a reinforcement phase. This type of particle-reinforced iron-based composite material has the advantages of low cost, relatively simple preparation process, isotropic performance and easy secondary processing. Ceramic particles can significantly improve the mechanical and friction and wear properties of the matrix material.
[0003] The traditional methods for preparing particle-reinforced iron-based composites mainly include: powder metallurgy, surface cladding and in-situ synthesis. However, traditional preparation processes often form too many carbide phases and intermetallic compounds, which significantly reduce the material performance and thus affect the service life. Moreover, the surface cladding method is only suitable for preparing high-wear-resistant surface coatings and cannot be used to prepare larger bulk materials. Spark plasma sintering technology, as an emerging rapid preparation method, has the advantages of fast, low temperature, density and low energy consumption and has attracted a lot of attention. Therefore, it is very necessary to explore the use of spark plasma sintering methods to quickly prepare ceramic particle-reinforced iron-based composites, so as to meet the needs of a large number of applications in mining, metallurgy, drilling and other fields.
[0004] TiC has excellent physical and chemical properties such as low density, high melting point, high hardness, wear resistance, corrosion resistance and good stability. TiC with a face-centered cubic structure has good wettability with the iron matrix at high temperatures and does not react chemically. 7 C 3 It has many advantages such as high melting point, high hardness, wear resistance and good stability. 7 C 3 As a reinforcing phase, it is expected to obtain ceramic particle reinforced iron-based composite materials with excellent properties such as higher hardness, high temperature resistance and wear resistance, which can be used in wear-resistant tools, tooling dies and parts in the fields of mining, metallurgy and drilling, as well as sealing rings of various pipes and pumps. Summary of the invention
[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a ceramic particle reinforced iron-based composite material and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a ceramic particle reinforced iron-based composite material, which comprises the following raw material components by mass percentage: Cr 7 C 310~20%, TiC 8~30%, and the balance is Fe powder.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic particle reinforced iron-based composite material, comprising the following steps:
[0009] S1. Weigh Cr according to the formula 7 C 3 powder, TiC powder and Fe powder are mixed and ball-milled to obtain a mixed powder;
[0010] S2, loading the obtained mixed powder into a graphite mold, applying pressure to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat;
[0011] S3, placing the pressed mold in a spark plasma sintering furnace for sintering to obtain a ceramic particle reinforced iron-based composite material.
[0012] Preferably, the Cr 7 C 3 The particle sizes of powder, TiC powder and Fe powder are all 240 mesh to 1340 mesh.
[0013] Preferably, in step S1, the ball milling conditions are: the ball milling speed is 200-300 r / min, the ball-to-material ratio is 1-10:1, the ball milling time is 12-18 h, and the grinding ball material is zirconia.
[0014] Preferably, in step S3, the specific process of the sintering treatment is: placing the pressurized mold in a spark plasma sintering furnace, evacuating to below 10 Pa, raising the temperature to 1100-1300°C at a heating rate of 80-100°C / min for sintering, keeping warm for 20-40 minutes, and maintaining the system sintering pressure at 30-40MPa during the insulation process, and then cooling.
[0015] Further preferably, the sintering temperature is 1100-1200°C, and the system sintering pressure is 30-35MPa;
[0016] Preferably, the cooling is to below 100°C.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) Compared with the traditional sintering process, the spark plasma sintering process used in the present invention has a higher efficiency ratio, thereby reducing energy consumption and environmental impact. At the same time, by utilizing the spark plasma sintering process, the preparation time is greatly shortened, the production efficiency is improved, and the sintering is performed at a lower temperature, which also avoids or reduces the overheating and grain coarsening of the material.
[0019] (2) Compared with as-cast high-chromium cast iron, the ceramic particle reinforced iron-based composite material prepared by the preparation method of the present invention has higher hardness and better wear resistance.
[0020] (3) The preparation method of the present invention has a simple process and low cost, and is suitable for industrial production. It is expected to further reduce the price of high-performance wear-resistant steel materials, and can be widely used in the fields of mining, metallurgy and drilling engineering, and therefore has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The microstructure diagram of the ceramic particle reinforced iron-based composite material prepared in Example 1;
[0023] Figure 2 The microstructure diagram of the ceramic particle reinforced iron-based composite material prepared in Example 2;
[0024] Figure 3 The microstructure diagram of the ceramic particle reinforced iron-based composite material prepared in Example 3;
[0025] Figure 4 This is a microstructure diagram of the ceramic particle reinforced iron-based composite material prepared in Example 4. DETAILED DESCRIPTION
[0026] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.
[0027] Example 1
[0028] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 10%, TiC 20%, and the balance Fe. The preparation method comprises the following steps:
[0029] S1. Weigh Cr according to the above mass ratio. 7 C 3powder (325 mesh), TiC powder (325 mesh) and Fe powder (325 mesh), and then the powders are ball-milled and mixed in a ball mill. The ball-milling conditions are as follows: the ball-milling speed is 260 r / min, the ball-to-material ratio is 5:1, the ball-milling time is 15 h, and the grinding ball material is zirconia, to obtain a mixed powder;
[0030] S2. Prepare a cylindrical graphite mold with an inner diameter of 50 mm, cover the inner wall of the sleeve and the upper and lower positions contacting the metal powder with graphite paper, and apply a mixture of boron nitride powder and alcohol on the coated graphite paper, then place the obtained mixed powder in the graphite mold, and use a pressure head to apply a certain pressure to the powder to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat;
[0031] S3, placing the graphite mold after pressure in a spark plasma sintering furnace, and then evacuating to below 10Pa, heating to 1200℃ at a heating rate of 100℃ / min, sintering, and keeping warm for 30min, and maintaining the system sintering pressure at 35MPa during the insulation process, cooling to below 100℃ after the insulation, unloading the pressure and sampling to obtain a ceramic particle reinforced iron-based composite material. The microstructure of the obtained ceramic particle reinforced iron-based composite material was scanned using a scanning electron microscope, and the results are shown in Figure 1 The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0032] Example 2
[0033] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 10%, TiC 10%, and the balance Fe. The preparation method comprises the following steps:
[0034] S1. Weigh Cr according to the above mass ratio. 7 C 3 powder (800 mesh), TiC powder (800 mesh) and Fe powder (240 mesh), and then the powders are ball-milled and mixed in a ball mill. The ball-milling conditions are as follows: the ball-milling speed is 200 r / min, the ball-to-material ratio is 5:1, the ball-milling time is 12 h, and the grinding ball material is zirconia, to obtain a mixed powder;
[0035] S2. Prepare a cylindrical graphite mold with an inner diameter of 50 mm, cover the inner wall of the sleeve and the upper and lower positions contacting the metal powder with graphite paper, and apply a mixture of boron nitride powder and alcohol on the coated graphite paper, then place the obtained mixed powder in the graphite mold, and use a pressure head to apply a certain pressure to the powder to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat;
[0036] S3, placing the graphite mold after pressure in a spark plasma sintering furnace, and then evacuating to below 10Pa, heating to 1200℃ at a heating rate of 100℃ / min, sintering, and keeping warm for 35min, and maintaining the system sintering pressure at 30MPa during the insulation process, cooling to below 100℃ after the insulation, unloading the pressure and sampling to obtain a ceramic particle reinforced iron-based composite material. The obtained ceramic particle reinforced iron-based composite material was scanned for microstructure using a scanning electron microscope, and the results are shown in Figure 2 The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0037] Example 3
[0038] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 20%, TiC 8%, and the balance Fe. The preparation method comprises the following steps:
[0039] S1. Weigh Cr according to the above mass ratio. 7 C 3 powder (1340 mesh), TiC powder (1340 mesh) and Fe powder (325 mesh), and then the powders are ball-milled and mixed in a ball mill. The ball-milling conditions are as follows: the ball-milling speed is 300 r / min, the ball-to-material ratio is 10:1, the ball-milling time is 12 h, and the grinding ball material is zirconia, to obtain a mixed powder;
[0040] S2. Prepare a cylindrical graphite mold with an inner diameter of 50 mm, cover the inner wall of the sleeve and the upper and lower positions contacting the metal powder with graphite paper, and apply a mixture of boron nitride powder and alcohol on the coated graphite paper, then place the obtained mixed powder in the graphite mold, and use a pressure head to apply a certain pressure to the powder to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat;
[0041] S3, placing the graphite mold after pressure in a spark plasma sintering furnace, and then evacuating to below 10Pa, heating to 1300℃ at a heating rate of 80℃ / min, sintering, and keeping warm for 30min, and maintaining the system sintering pressure at 30MPa during the insulation process, cooling to below 100℃ after the insulation, unloading the pressure and sampling to obtain a ceramic particle reinforced iron-based composite material. The microstructure of the obtained ceramic particle reinforced iron-based composite material was scanned using a scanning electron microscope, and the results are shown in Figure 3 The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0042] Example 4
[0043] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 15%, TiC 30%, and the balance Fe. The preparation method comprises the following steps:
[0044] S1. Weigh Cr according to the above mass ratio. 7 C 3 powder (240 mesh), TiC powder (240 mesh) and Fe powder (1340 mesh), and then the powders are ball-milled and mixed in a ball mill. The ball-milling conditions are as follows: the ball-milling speed is 260 r / min, the ball-to-material ratio is 1:1, the ball-milling time is 18 h, and the grinding ball material is zirconia, to obtain a mixed powder;
[0045] S2. Prepare a cylindrical graphite mold with an inner diameter of 50 mm, cover the inner wall of the sleeve and the upper and lower positions contacting the metal powder with graphite paper, and apply a mixture of boron nitride powder and alcohol on the coated graphite paper, then place the obtained mixed powder in the graphite mold, and use a pressure head to apply a certain pressure to the powder to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat;
[0046] S3, placing the graphite mold after pressure in a spark plasma sintering furnace, and then evacuating to below 10Pa, heating to 1100℃ at a heating rate of 100℃ / min, sintering, and keeping warm for 40min, and maintaining the system sintering pressure at 40MPa during the insulation process, cooling to below 100℃ after the insulation, unloading the pressure and sampling to obtain a ceramic particle reinforced iron-based composite material. The obtained ceramic particle reinforced iron-based composite material was scanned for microstructure using a scanning electron microscope, and the results are shown in Figure 4 The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0047] Comparative Example 1
[0048] It is basically the same as Example 1, except that in step S3, the sintering temperature is 1000°C.
[0049] Finally, a very loose ceramic particle reinforced iron-based composite material sample was obtained. Macroscopic holes were visible inside, the powder was not completely combined together, and there was obvious powder loss during the grinding and polishing process. Therefore, it was impossible to perform experimental measurements such as Vickers hardness and three-body wear performance using a Vickers hardness tester and a three-body wear testing machine.
[0050] Comparative Example 2
[0051] It is basically the same as Example 1, except that in step S3, the sintering temperature is 1400°C.
[0052] Since the C element in the graphite mold and graphite paper penetrates into the sample under the action of high temperature sintering, a ceramic particle reinforced iron-based composite material with a higher C content is finally obtained. The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester, and the test results are shown in Table 1.
[0053] Comparative Example 3
[0054] The method is basically the same as Example 1, except that in step S3, the sintering pressure of the system is maintained at 20 MPa during the heat preservation process. Finally, a relatively loose ceramic particle reinforced iron-based composite material is obtained. Macroscopic holes can be seen in the sample, the powder is not completely combined together, and powder falls off during the grinding and polishing process, so the ceramic particle reinforced iron-based composite material cannot be tested using a Vickers hardness tester and a three-body wear tester.
[0055] Comparative Example 4
[0056] It is substantially the same as Example 1, except that, in step S3, the sintering pressure of the system is maintained at 60MPa during the heat preservation process. Ceramic particles are reinforced with iron-based composite materials, but the material sample is tightly connected to the graphite mold and cannot be effectively demoulded. And there are obvious signs of carburization on the surface of the material sample, which is very brittle. The core sample cannot meet the size requirements of the three-body wear tester after cutting, so that the three-body wear performance test cannot be performed on it. However, Vickers hardness tester can be used for Vickers hardness test, and the test results are shown in Table 1.
[0057] Comparative Example 5
[0058] The method is basically the same as Example 1, except that in step S3, the holding time is 10 minutes. Finally, a relatively loose ceramic particle reinforced iron-based composite material is obtained, and macroscopic holes are visible in the material sample, the powders are not completely combined together, and powder falls off during the grinding and polishing process, so it is impossible to use a Vickers hardness tester and a three-body wear tester to perform experimental measurements of Vickers hardness and three-body wear performance. However, a Vickers hardness tester can be used for Vickers hardness testing, and the test results are shown in Table 1.
[0059] Comparative Example 6
[0060] It is substantially the same as Example 1, except that, in step S3, the holding time is 60 min. Finally, a ceramic particle reinforced iron-based composite material is obtained, and the material sample is tightly connected to the graphite mold and cannot be effectively demoulded. And there are obvious signs of carburization on the surface of the sample, which is very brittle. The sample of the core portion cannot meet the size requirements of the three-body wear tester after cutting, so that the three-body wear performance test cannot be performed on it, but a Vickers hardness tester can be used for Vickers hardness test, and the test results are shown in Table 1.
[0061] Comparative Example 7
[0062] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 10%, TiC 20%, and the balance Fe. The preparation method comprises the following steps:
[0063] S1. Weigh Cr according to the above mass ratio. 7 C 3 powder (325 mesh), TiC powder (325 mesh) and Fe powder (325 mesh), and then the powders are ball-milled and mixed in a ball mill to obtain a mixed powder, and then cold-pressed to form a green body;
[0064] S2, place the green body in a vacuum sintering furnace, and then evacuate to 10 -1 Pa, the temperature was raised to 1200°C at a heating rate of 10°C / min, sintered, and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to below 50°C and sampled to obtain a ceramic particle reinforced iron-based composite material. The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0065] Comparative Example 8
[0066] A ceramic particle reinforced iron-based composite material, comprising the following raw material components by mass percentage: Cr 7 C 3 10%, TiC 20%, and the balance Fe. The preparation method comprises the following steps:
[0067] S1. Weigh Cr according to the above mass ratio. 7 C 3 powder (325 mesh), TiC powder (325 mesh) and Fe powder (325 mesh), then the powders are ball-milled and mixed in a ball mill to obtain a mixed powder, which is then cold-pressed into a blank;
[0068] S2, place the green body in a vacuum sintering furnace, and then evacuate to 10 -1 Pa, the temperature was raised to 1500°C at a heating rate of 10°C / min, sintered, and kept warm for 60 minutes. After the end of the heat preservation, it was cooled to below 50°C and sampled to obtain a ceramic particle reinforced iron-based composite material. The ceramic particle reinforced iron-based composite material was tested using a Vickers hardness tester and a three-body wear tester. The test results are shown in Table 1.
[0069] Depend on Figure 1-4 The results show that the ceramic particle reinforced iron-based composite materials obtained in Examples 1-4 all contain carbide Cr 7 C 3 Phase, TiC face-centered cubic phase and austenite phase are equal, and do not contain other carbide phases.
[0070] Table 1. Vickers hardness and three-body wear performance test results of ceramic particle reinforced iron-based composite materials prepared in Examples 1-4 and Comparative Examples 1-8
[0071]
[0072]
[0073] From the results in Table 1, it can be seen that the Vickers hardness HV of the ceramic particle reinforced iron-based composite material obtained in Example 1 is 1359±40, and the wear loss in 150 minutes is 0.31±0.05. In Comparative Example 1, due to the low sintering temperature, the powders cannot be well combined, resulting in obvious defects such as powder particles and holes in the obtained sample, which cannot be used for subsequent detection and analysis. This shows that the sintering temperature of the ceramic particle reinforced iron-based composite material cannot be too low; in Comparative Example 2, due to the high sintering temperature, the C element in the graphite mold and graphite paper penetrates into the sample and the diffusion rate of the C element is very high at high temperature and can enter the core of the sintered sample, thereby significantly increasing the C content of the sample, causing the sample phase to change, and more brittle carbide phases appear, resulting in a significant decrease in Vickers hardness and wear resistance. The above analysis results show that the sintering temperature when preparing ceramic particle reinforced iron-based composite materials needs to be controlled within a certain temperature range.
[0074] In Comparative Example 3, due to the low sintering pressure, some powders will not be well combined into blocks, and there are still obvious defects such as powder particles and holes in the sample, which cannot be used for subsequent detection and analysis. This shows that the sintering pressure at a certain sintering temperature when preparing ceramic particle-reinforced iron-based composite materials cannot be set too low. In Comparative Example 4, due to the high sintering pressure, the graphite mold and the sample will be closely combined together, and the C element in the graphite mold and graphite paper will penetrate into the sample. The size of the core obtained after removing the carburized layer on the surface of the sample is small, and only Vickers hardness detection can be carried out, and the Vickers hardness result of the core sample is significantly lower than that of Example 1, which may be attributed to the fact that some C elements still infiltrate and induce phase changes. The above analysis results show that the sintering pressure for preparing ceramic particle-reinforced iron-based composite materials needs to be controlled within a certain numerical range to ensure that a sample with good density and ideal size is obtained.
[0075] In Comparative Example 5, due to the short heat preservation and pressure holding time, each powder will not be well combined into a block, and there are still obvious defects such as powder particles and holes in the sample, so it cannot be used for subsequent detection and analysis, which shows that the heat preservation and pressure holding time at a certain sintering temperature and sintering pressure when preparing ceramic particle reinforced iron-based composite materials cannot be set too short. In Comparative Example 6, due to the long heat preservation and pressure holding time, the graphite mold and the sample will be closely combined together, and the C element in the graphite mold and graphite paper will penetrate into the sample. The size of the core obtained after removing the carburized layer on the surface of the sample is small, so only Vickers hardness test can be carried out, and the Vickers hardness result of the core sample is significantly worse than that of Example 1, which may be attributed to the fact that some C elements still infiltrate and induce phase changes. The above analysis results show that the heat preservation and pressure holding time of ceramic particle reinforced iron-based composite materials needs to be controlled within a certain numerical range to ensure that a sample with good density and ideal size is obtained.
[0076] Comparative Examples 7 and 8 use a traditional vacuum sintering furnace to prepare ceramic particle reinforced iron-based composite materials. Among them, compared with Example 1, the sintering temperature and sintering time of Comparative Example 7 are the same, but Comparative Example 7 does not apply pressure during the sintering process, while Example 1 keeps a pressure of 35MPa on the sample during the sintering process. The sintering results show that the powders in Comparative Example 7 failed to combine well into a block, and there are still obvious defects such as powder particles and holes in the sample, so it cannot be used for subsequent detection and analysis, which shows that the sintering temperature and time need to be appropriately increased when using the traditional sintering method to prepare ceramic particle reinforced iron-based composite materials.
[0077] Comparative Example 8 significantly increases the sintering temperature and time on the basis of Comparative Example 7. The Vickers hardness and wear resistance of Comparative Example 8 are significantly lower than those of Example 1, because the ceramic particle reinforced iron-based composite material prepared in Comparative Example 8 still has inevitable defects such as holes inside and the grains are coarse due to the excessively high sintering temperature.
[0078] In addition, compared with as-cast high-chromium cast iron, the ceramic particle-reinforced iron-based composite materials prepared in Examples 1 to 4 of the present invention have higher Vickers hardness and better wear resistance, and can therefore be used as high-performance iron-based composite materials in mining, metallurgy and drilling engineering, and have very broad application prospects.
[0079] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.
Claims
1. A ceramic particle reinforced iron-based composite material, characterized in that: Calculated by mass percentage, the raw material components include: 10-20% of Cr7C3, 8-30% of TiC, and the balance of Fe.
2. A method for preparing a ceramic particle reinforced iron-based composite material as claimed in claim 1, characterized in that: The following steps are involved: S1. Weigh Cr7C3 powder, TiC powder and Fe powder according to the formula, mix and ball-mill to obtain a mixed powder; S2, loading the obtained mixed powder into a graphite mold, applying pressure to ensure that the powder particles are tightly packed and the upper and lower surfaces are flat; S3, placing the pressed mold in a spark plasma sintering furnace for sintering to obtain a ceramic particle reinforced iron-based composite material.
3. The ceramic particle reinforced iron-based composite material according to claim 2, characterized in that: The particle size of the Cr7C3 powder is 240 mesh to 1340 mesh, the particle size of the TiC powder is 240 mesh to 1340 mesh, and the particle size of the Fe powder is 240 mesh to 1340 mesh.
4. The method for preparing a ceramic particle reinforced iron-based composite material according to claim 2, characterized in that: In step S1, the ball milling conditions are: the ball milling speed is 200-300 r / min, the ball-to-material ratio is 1-10:1, the ball milling time is 12-18 h, and the grinding ball material is zirconia.
5. The method for preparing a ceramic particle reinforced iron-based composite material according to claim 2, characterized in that: In step S3, the specific process of the sintering treatment is: placing the pressurized mold in a spark plasma sintering furnace, evacuating to below 10Pa, raising the temperature to 1100-1300°C at a heating rate of 80-100°C / min for sintering, keeping warm for 20-40 minutes, and maintaining the system sintering pressure at 30-40MPa during the insulation process, and then cooling.
6. The method for preparing a ceramic particle reinforced iron-based composite material according to claim 5, characterized in that: The cooling is to below 100°C.
Citation Information
Patent Citations
TiC-Cr7C3-CNTs / iron based surface composite material and preparation method thereof
CN104388928A
Lightweight piston pin and method for manufacturing the lightweight piston pin
CN106513686A
Multiphase ceramic particle dispersion reinforced iron-based composite material and preparation method thereof
CN113174542A
Structural body of valve-insert constituent for internal combustion engine
JP1995259517A
Wear and corrosion resistant iron based coating
WO2022223835A1